PREDIKSI JARAK VERTIKAL ZONA BIJIH ENDAPAN NIKEL LATERIT UNTUK PERHITUNGAN CADANGAN DAERAH KONSESI PT. INCO SOROAKO - Ilyas (NIM : 22199013), Asran
Abstract : One of the problems that's coming up on mining activities and reserves evaluation for the lateritic nickel deposit in PT. INCO Soroako is "how to find another way that could be used to estimate the height between the cover of boulder peridotite in the ore zone that can't be penetrated by the auger machine until' the bedrock and could be to predict the value of the chemical content of nickel on every one meter as a vertical". The final outcome will be use by PT. INCO to calculate the reserves of the deposit and mining activities. The writer try to help this problem in that way by application of the statistical science, geostatistic, and numerical analysis in solving simulation with mathematics in data modelling. Data modelling conducted by regression method approach. The model had been designed on program languange in Fortran. From the outcome of the data validation, the average of the differentiation between the real and the prediction content of nickel is about 0,6 weight % and the average of the height between the real and the prediction ore zone is about 0 until 3 m.